Using the CSM‐CROPGRO‐Peanut Model to Simulate Late Leaf Spot Effects on Peanut Cultivars of Differing Resistance. (1st September 2013) - Singh, Maninder P.; Erickson, John E.; Boote, Kenneth J.; Jones, James W.; Tillman, Barry L.; van Bruggen, Ariena H. C.
Abstract : Late leaf spot (LLS) caused by Cercosporidium personatum (Berk. and Curt.) Deighton leads to significant reductions in peanut ( Arachis hypogaea L.) yield worldwide. This study was conducted to improve the mechanisms and methods by which LLS effects on defoliation and photosynthesis are linked to the CSM‐CROPGRO‐Peanut model for simulating growth and yield reductions in peanut cultivars. Field experiments were conducted in 2008 and 2009 to collect data on the effects of LLS on biomass accumulation and partitioning, leaf necrosis and defoliation, and total canopy photosynthesis (TCP) in peanut cultivars with more (York) and less (Carver) quantitative resistance to LLS. After incorporating LLS damage as defoliation percentage and necrotic area, the model accurately simulated crop growth and development for both cultivars despite different disease dynamics. Simulated TCP and leaf, total crop, and pod yield values were in good agreement with measured data. A modification in the model code to directly reduce leaf photosynthesis and quantum efficiency according to empirical observations resulted in improved simulations of LLS effects on growth and yield. Correlations among measured defoliation and necrotic area with disease ratings indicated that visual disease ratings could be successfully used to estimate necrosis and defoliation for model inputs. Results indicated that the CSM‐CROPGRO‐Peanut model has adequate capability to simulate LLS effects on growth and yield in peanut cultivars with differing levels of resistance to LLS when inputs on canopy necrotic area and defoliation are provided.